2020
DOI: 10.1186/s40621-020-00271-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between family cohesion and disability following blunt trauma: findings from a level-I trauma center in Saudi Arabia

Abstract: Background: Injuries pose a significant burden on population health of Saudi Arabia. Even in nonfatal injuries, the burden varies from temporary to permanent disabilities. Health outcomes following injuries can vary, and predictors of recovery from disability are not well understood. In the Kingdom, family values and cohesion can differ from other countries due to several factors, including religious beliefs and cultural traditions. Learning about predictors of injury recovery can improve prevention as well as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The most studied condition was diabetes mellitus (n=4), [23][24][25][26] followed by musculoskeletal disorders, back pain, and injuries (n=3). [27][28][29] The remaining articles focused either on a specific condition, such as urinary…”
Section: Comparison Of Results By Condition or Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The most studied condition was diabetes mellitus (n=4), [23][24][25][26] followed by musculoskeletal disorders, back pain, and injuries (n=3). [27][28][29] The remaining articles focused either on a specific condition, such as urinary…”
Section: Comparison Of Results By Condition or Treatmentmentioning
confidence: 99%
“…Only three of the thirteen official administrative Saudi Arabian regions have been studied: Riyadh, 26,29,30,34 Makkah, 24,27,32 and Dammam. 23 Riyadh likely accounts for more publications, being the capital of the KSA and home to many hospitals and universities.…”
Section: Comparison Of Results By Regionmentioning
confidence: 99%
“…To explain this finding, it can be stated that positive motherchild interactions improve the mental health status of Studies have also revealed that the families of children with learning disabilities report high levels of conflict and low levels of cohesion. Moreover, a sense of parenting inadequacy may gradually affect other private parts of the lives and marital relationships of the mothers of these children over time (Gerstein & Crnic 2018;Mohammed Almarwani et al 2020). As a result, parents, especially the mothers of such children naturally encounter further problems.…”
Section: Discussionmentioning
confidence: 99%